The Challenge of Integrating Science and Religion in Indonesia and Malaysia - Hadi, Saiful; Affani, Syukron; Ayman Al-Akiti, Muhammad (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article discusses the implementation and problems of integration of science and religion in Madurese Islamic boarding schools and Islamic education institutions in Selangor, Malaysia. The development of a modern Muslim society requires Islamic education institutions to reform and actualize their syllabus. Using a phenomenological approach, the study data were collected through interviews, observations, and online materials. The main research samples are IISM School Gombak, Al Hamra Integrated School, Akademi Tahfiz Al-Hidayah in Kuala Lumpur, Malaysia and Pondok Pesantren Al Amien Prenduan in Sumenep, Pondok Pesantren Annuqayah Sumenep, and Pondok Pesantren Darul Ulum Banyuanyar Pamekasan in Madura, Indonesia. It was found that the Islamic boarding schools in Madura implement adoptive-adaptive formal integration where some parts of the education subsystem are carried out separately, while the Islamic schools in Selangor follow a holistic approach. Both systems attempt to offer an inclusive syllabus; however, the integration of science in Madurese pesantren leans more towards constructive integration with concurrent traditionalist elements, while Islamic schools in Selangor have adopted a more modern and progressive syllabus.